Construction of PEG-based amphiphilic brush polymers bearing hydrophobic poly(lactic acid) side chains via successive RAFT polymerization and ROP. Issue 19 (25th April 2016) - Qian, Wenhao; Song, Xuemei; Feng, Chun; Xu, Peicheng; Jiang, Xue; Li, Yongjun; Huang, Xiaoyu
Abstract : This article reports the synthesis of PEG- b -(PAA- g -PLA) amphiphilic brush polymers by the combination of RAFT polymerization and organocatalytic ROP, which could self-assemble into spheres for sustained release of doxorubicin. Abstract : A series of well-defined amphiphilic brush polymers containing hydrophilic poly(ethylene glycol) (PEG) and hydrophobic poly(lactic acid) segments was synthesized by the combination of reversible addition–fragmentation chain transfer (RAFT) polymerization, ring opening polymerization (ROP), and the grafting-from strategy. tert -Butyl 2-((4-hydroxybutanoyloxy)methyl)acrylate ( t BHBMA) monomer containing a ROP initiation group (–OH) was first RAFT block copolymerized using a PEG-based chain transfer agent to form two well-defined PEG- b -P t BHBMA diblock copolymers ( M w / M n ≤ 1.10) bearing pendant hydroxyls in every repeated unit of P t BHBMA segment. Both diblock copolymers directly initiated ROP of lactide by the pendant hydroxyls to provide well-defined poly(ethylene glycol)- b -(poly( tert -butyl acrylate)- g -poly(lactic acid)) (PEG- b -(P t BA- g -PLA)) brush polymers ( M w / M n ≤ 1.16) without post-polymerization functionality transformation. The target well-defined poly(ethylene glycol)- b -(polyacrylic acid)- g -poly(lactic acid) (PEG- b -(PAA- g -PLA)) amphiphilic brush polymers were achieved by the selective acidolysis of hydrophobic P t BA backbone ( tert -butyoxycarbonyls) into hydrophilic PAA backbone (carboxyls) using trifluoroacetic acid. PEG- b -(PAA- g -PLA) brush polymers could self-assemble into spheres with a size of ca . 70–110 nm in aqueous media as evidenced by DLS and TEM. The drug (doxorubicin) loading ability of PEG- b -(PAA- g -PLA) brush polymers was investigated preliminarily by measuring the in vitro cell (SMMC-7721 and SH-SY5Y) viabilities, which showed higher cytotoxicity compared to free DOX.